Faktor sosial ekonomi yang berhubungan dengan tingkat asupan zat yodium pada ibu hamil di daerah endemik - Sultan Akbar Toruntju, Hamam Hadi, Toto Sudargo (Berita Kedokteran Masyarakat (BKM), 2005)
Background: Many efforts have been made to overcome Iodine Deficiency Disease but its prevalence in Indonesia is still high. Total Goiter Rate (TGR) of elementary school children is rising from 9.8% in 1998 to 10.3% in 2003. In Gunungkidul District TGR is as high as 12.2% in 2002. The most possible cause is low iodine consumption which is 73.08% in 2003. Other possible causes are low iodine intake, goitrogenic consumption, low social economic life, knowledge, attitude and inappropriate eating behavior, etc. Objectives: To know the relationship between social economic factors, knowledge, attitude and iodine consumption behavior with iodine intake of pregnant mothers. Methods: The study was a cross sectional type which was done from October — December 2004 at 6 sub districts of IDD endemic area, Gunungkidul District. Samples consisted of 258 pregnant mothers. Iodine intake data as dependent variable were collected using Food Frequency Questionnaires. There were 7 independent variables: mothers' education, income, and food expenditure, n umber of dependants, knowledge, and attitude and iodine consumption behavior which were collected using scored questionnaires. Pearson Correlation and Odd Ratio were used for bivariate analysis whereas Multiple Regression was used for multivariate analysis. Results: Average level of education was 2.65% (elementary school graduate, junior high school drop out). Average family income was Rp772.712,00 (>regional minimum wage). Average food expenditure was Rp339.380,00 (52.9% of total expenditure and 43.9% of total family income). Average number of dependants was 5 persons. Average iodine intake was 139.4 pg/day. Average knowledge, attitude and behavior score was 71.0, 109.7 and 73.5 subsequently. Correlation analysis with odd ratio showed: there was relationship between income and iodine intake (r2 = 0.252; OR=5.7); there was relationship between attitude and iodine intake (r2 = 0.13; OR =2.1); there was relationship between behavior and iodine intake (r2= 0.95; OR =11.2). Linear regression analysis showed that behavior variable had the greatest contribution to iodine intake. Conclusion: There was relationship between knowledge and iodine intake. There was relationship between food expenditure and iodine intake. There was relationship between number of dependants and iodine intake. There was relationship between attitude and iodine intake and there was relationship between behavior and iodine intake. There was relationship between knowledge and iodine intake. Keywords: education, income, food expenditure, dependants, knowledge, attitude and behavior, iodine intake, pregnant mothers